Zikir dan Ketenangan Jiwa: Telaah atas Pemikiran Al-Ghazali - Rahmat Ilyas (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2017)
The human soul is the key to the success of a person in achieving his goal. Without a healthy and calm soul it would be difficult for a man to obtain and achieve his purpose in life. This dhikr is aimed at reversing the whole human character and diverting one's main attention from the beloved world to an ever-unrecognized afterlife. By often dhikr either with oral or with the heart will be obtained inner experience which is not every person experience it. With the dhikr of the hijab that is in the heart of the man who always stuck in the material will open and make a man who always and clever thankful for all the blessings, graces and gifts obtained by him, and clean the hearts of human and human souls from the turmoil of defilement and animal behavior.